Investigation on structure stability and damage mechanism of cemented paste backfill under the coupling effect of water-static load - Zhiyi Liu; Deqing Gan; Haikuan Sun; Zhenlin Xue; Youzhi Zhang (Alexandria Engineering Journal)
Cemented paste backfill (CPB) is easy to withstand the coupling effect of the mining operation equipment's crushing, water immersion, forming all kinds of intrinsic or extrinsic defects affecting its load-bearing capacity. In this paper, the initial immersion age and immersion time were used as variables, the damage and uniaxial compression characteristics of CPB under the coupling effect of water-static load were explored. Results show that the damage of water-immersed CPB under static load are mainly affected by water lubrication and pore water pressure and it improves the plastic deformation of CPB and weakens the energy storage capacity. When the initial immersion age was 3d, the effect is more significant. Water immersion increases the rate of damage with strain before peak strain and decreases the rate of damage with strain after peak strain. The strength of CPB varies from 0.3 MPa to 0.8 MPa at the same initial immersion age. The damage constitutive model of CPB under water-static load coupling is established, and the damage mechanism is revealed. Compared with the immersion time, reducing the initial immersion age is the key factor to improve the structure stability of CPB.